Dampak biologis kontaminasi mikroplastik terhadap kesehatan manusia: Refleksi QS. Al-A’raf tentang larangan merusak bumi - Aminatuzzahro’, Umi (Maliki Interdisciplinary Journal, 2026)
Plastic waste has become a serious environmental problem due to its non-biodegradable nature and its ability to break down into microplastic particles smaller than 5 mm, which can spread through water, soil, and air, and enter the human food chain via fish, vegetables, and tubers. Microplastics pose biological risks to organisms, enable the bioaccumulation of harmful substances, and can alter ecosystem structures, as evidenced by contamination found in milkfish in Sidoarjo and potatoes in Malang Raya, indicating their potential transfer to humans. Mitigation efforts include proper plastic waste management, sustainable agricultural practices, environmental monitoring, and public education. From an Islamic perspective, the presence of microplastics emphasizes human responsibility as caliphs to maintain the balance and preservation of the Earth, as stated in QS. Al-A’raf verse 56. Addressing microplastic pollution requires an integrated approach combining scientific knowledge, social practices, and ethical principles to ensure a clean, healthy, and sustainable environment.